Poverty and the Role of Islam in Reducing Poverty - Gul Mazloum Yar, Fayaz; Ullah Nasih, Ihsan (Journal of World Science, 2023)
Poverty is one of the greatest concerns in all societies and economic systems. It is a negative phenomenon that threatens life. Economic schools of thought have presented various approaches to overcome poverty, but so far have not succeeded in eradicating it from human life. This occurrence is referred to as an unpleasant complication. Poverty is one of the most significant and persistent problems in both developed and developing countries, including Islamic countries. The purpose of this research is to examine the role of Islam in reducing poverty. The research method used in this study is descriptive-analytical, and the necessary information was gathered from library sources and through the use of the Delphi method. The research findings indicate that in this study, the concept of poverty and its impacts are analyzed through verses from the Quran and Hadith. Findings include the definition of poverty and the gap between the rich and the poor, which is a major concern in the fields of economics and public policy. Despite being widespread, poverty is not limited to economic aspects alone but also encompasses cultural, social, and educational poverty. Analysis from the perspective of financial development highlights the importance of understanding its overall impact.